Tinjauan Modernisasi Pembangunan Pada Desa Jatiroke Kabupaten Sumedang Tahun 2025 - Algiffary, Muhammad Hakim; R, Rudiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Abstract This study aims to examine the stages of development modernization that occurred in Jatiroke Village, Sumedang Regency in 2025. Using a qualitative-descriptive approach and literature study method, this study analyzes the village development process based on the theory of economic growth stages proposed by W.W. Rostow. The results of the study indicate that Jatiroke Village has passed the traditional stage and the prerequisite stage for take-off, and is at the take-off stage. This indication is reflected in the development of physical infrastructure, strengthening the local economy through MSMEs, and the implementation of village information systems. However, a number of obstacles such as budget limitations, community participation, and digitalization that have not had a direct impact on welfare are important notes. Therefore, it is necessary to optimize development planning, increase investment, and industrialization strategies to encourage Jatiroke Village towards a more mature stage of development.